ENDOWMENT AND WAQF FUNDS IN MALAYSIAN HIGHER EDUCATION: A CONCEPTUAL STUDY - Hasbullah, Nurul Adilah; Ab Rahman, Asmak (Jurnal Syariah, 2021)
Higher Education Institutions (HEIs) require sustainable sources of income to fund operating costs. The role of endowment funds has always been significant in providing financial sources to these institutions. In Islam, an endowment is known as waqf. As the differences in these two types of funds are found to be indistinctive, this study explores and highlights the atypical concepts. The method of library research has been used to acquire relevant reference materials to discuss the concepts. This paper has identified several aspects that distinguished these two funds, which include the element of perpetuity element, rights of ownership, and governance (law, structure, trustee, need permission, and income sharing).